Beta-lactamase binding to blip and blip based peptides - Doğan, Aslıgül. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Extensive use of antimicrobial agents has generated selective pressure on bacteria and resulted in development of resistance to beta-lactam antibiotics. The main resistance mechanism of bacteria is the production of beta-lactamase enzymes that can hydrolyze the beta-lactam ring and render the antibiotic inactive before it reaches the target. It is important to find an inhibitor to disable the beta-lactamase enzyme in order to benefit from beta-lactam antibiotics effectively against bacteria. BLIP is an effective beta-lactamase inhibitor but it exhibits different binding affinities to TEM-1 and SHV-1 beta-lactamases despite their 68% sequence identity. Molecular Dynamics simulations were performed in order to investigate the features that lead to the difference in binding affinity of BLIP to these two beta-lactamases. It was found that H10 helix (residues 218 to 230) and omega loop (residues 161 to 179) and especially residue 175, which is aspargine in TEM-1 and glycine in SHV-1, respond differently to BLIP binding in TEM-1 and SHV-1. The relevance of the H10 helix to the difference in binding affinity was further investigated by performing MD simulations on the TEM-1 W229A mutant in the apo and BLIP bound forms. In the second part of the work, peptides based on the BLIP loop (residues 45-52), that inserts into the beta-lactamase active site were used in MD simulations to investigate their binding potential and to study their interaction mechanism. Peptides were designed with different residue mutations and their binding to TEM-1 was investigated. Peptide that was based on 45 to 53 residues of BLIP and that has the G48F mutation is the peptide that exhibits tightest binding among the designed BLIP based peptides. This peptide can be used as a template for future studies to design new peptides with different residue mutations to enhance the binding affinity.
Keywords: Beta lactamases -- Inhibitors.; Drug resistance in microorganisms.; Beta lactam antibiotics.